2006
DOI: 10.1108/01443570610691111
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ISO 9001 on firms' productive efficiency

Abstract: Purpose -This work sets out to explore the effects of ISO 9001 on productive efficiency of firms. Design/methodology/approach -A sample of 1,572 firms from three Greek manufacturing industries is used for empirical work. The firms are from the food and beverages industries, the machineries industries as well as from the electrical and electronics appliances manufacturing industries and include both adopters and non-adopters of ISO 9001. A stochastic frontier methodological approach is adopted and the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 35 publications
(39 reference statements)
3
48
0
3
Order By: Relevance
“…Some researchers and authors state that implementation and certification is a paper-driven process of limited value, and it does not have an impact on firm performance, thus it may be considered as a marketing cue (Tzelepis et al, 2006). As confirmed by Gotzamani (2010), ISO 9000 research has shown that the major motive for certification comes from global external pressures, since companies cannot do business in Europe or other countries without first being certified.…”
Section: Third Party Auditingmentioning
confidence: 95%
See 1 more Smart Citation
“…Some researchers and authors state that implementation and certification is a paper-driven process of limited value, and it does not have an impact on firm performance, thus it may be considered as a marketing cue (Tzelepis et al, 2006). As confirmed by Gotzamani (2010), ISO 9000 research has shown that the major motive for certification comes from global external pressures, since companies cannot do business in Europe or other countries without first being certified.…”
Section: Third Party Auditingmentioning
confidence: 95%
“…In some cases, the supply and demand drivers support the decision on adopting a quality or other assurance scheme (Tsekouras, Dimara, & Skuras, 2002). Looking at food safety and quality in a wider perspective, the decision to adopt an assurance scheme may be the outcome of a complex push and pull process of simultaneously acting forces applied by external parties such as the final consumers, the intermediate consumers (other firms down the supply chain) or by a firm's own management (Tzelepis, Tsekouras, Skuras, & Dimara, 2006). As a result of the risks in the food supply chain, various assurance schemes have been developed and are present worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Implementation results in improved communication between employees, cost savings, reduced paper work, greater competitive advantage, more organized design and output and access to global markets (Peach, 1995). Tzelepis, Tsekouras, Skuras, and Dimara (2006), on the basis of an econometric analysis of Greek firms, conclude that ISO 9001 increases productive efficiency. The World Bank (1999, Box 2.1) cites evidence that amongst 93 major Brazilian enterprises surveyed in 1994, 55 per cent increased productivity as a result of ISO 9000 certification, 35 per cent improved the standardization of processes, 31 per cent increased employee participation in quality control and more than 20 per cent reported an increase in employee satisfaction.…”
Section: Iso 9000mentioning
confidence: 97%
“…The benefits of being certified also extend to non-financial performance indicators like growth in volume of production and productivity. Indeed, certified firms have been found to grow faster in terms of sales, productivity, employment, and wages (Terlaak and King, 2006;Levine and Toffel, 2010;Tzelepis, Tsekouras, Skuras, et al, 2006). The positive effects of firms obtaining certifications has also been researched and documented for developing countries.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%